Design of NiAl2O4 cellular monoliths for catalytic applications. (5th March 2017) - Vitorino, Nuno M.D.; Kovalevsky, Andrei V.; Ferro, Marta C.; Abrantes, João C.C.; Frade, Jorge R.
Abstract: This work focuses on designing highly-porous cellular NiAl2 O4 -based spinel ceramics through combined suspension emulsification/reactive sintering and further decoration of the pore surfaces by Ni nanoparticles for potential applications in heterogeneous catalysis. Due to kinetic limitations and specific porous structure, the reduction occurs without affecting the integrity of the cellular monoliths. The reaction mechanism, assessed by XRD and TEM/EDS, includes both partial decomposition and reduction, resulting in the formation of metastable Al-enriched phases, mainly NiAl32 O49, and metallic Ni phase, respectively. The results suggest that the cellular bulk framework can be decorated with Ni catalyst in a controlled way, by proper selection of the initial cation stoichiometry of the NiAl2 O4 spinel and appropriate reduction conditions. In selected conditions the reduction results in Ni nanoparticles of various dimension scales, finely dispersed at the pore surfaces, with a significant fraction below 50 nm, as confirmed by TEM/EDS. The results of thermodynamic analysis emphasize that the redox tolerance of the spinel phase is dependent on the Ni:Al activity ratio, suggesting the prospects for tuning the catalytic activity and stability by designing the initial composition and resulting content of metallic Ni and Ni- and Al-containing metastable phases. Graphical abstract: Highlights: Cellular spinel-based monoliths were prepared by suspension emulsification, reactive sintering and reduction. Flexible design of NiAl2 O4 -based catalysts in terms of redox stability and catalytic activity. New guidelines for controlled modification of the porous ceramic framework with nanostructured Ni are proposed.